2018
DOI: 10.15195/v5.a2
|View full text |Cite
|
Sign up to set email alerts
|

Last Name Selection in Audit Studies

Abstract: Abstract:In this article, we build on Gaddis (2017a) by illuminating a key variable plausibly related to racial perceptions of last names-geography. We show that the probability that any individual belongs to a race is conditional not only on their last name but also on surrounding racial demographics. Specifically, we demonstrate that the probability of a name denoting a race varies considerably across contexts, and this is more of a problem for some names than others. This result has two important implicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 20 publications
(29 reference statements)
0
29
0
Order By: Relevance
“…Second, we still have limited information about the signaling power of names. Although existing work has not focused explicitly on the perceptions of decision makers, scholars have found that racialethnic perceptions from names vary by a host of demographic characteristics and geographic location (Crabtree and Chykina 2018;Gaddis 2017aGaddis , 2017b. Decision makers, like human resources professionals, likely are exposed to a larger quantity and wider variety of names.…”
Section: Understanding the "How" Aspect Of Racial-ethnic Discriminationmentioning
confidence: 99%
“…Second, we still have limited information about the signaling power of names. Although existing work has not focused explicitly on the perceptions of decision makers, scholars have found that racialethnic perceptions from names vary by a host of demographic characteristics and geographic location (Crabtree and Chykina 2018;Gaddis 2017aGaddis , 2017b. Decision makers, like human resources professionals, likely are exposed to a larger quantity and wider variety of names.…”
Section: Understanding the "How" Aspect Of Racial-ethnic Discriminationmentioning
confidence: 99%
“…Census Bureau, 2012). Crabtree and Chykina (2018) examined the last names from Gaddis (2017) to identify geographically robust racially distinct last names. Frequency data from the Census was used to show that these last names were predominately used by one race.…”
Section: Methodsmentioning
confidence: 99%
“…To increase our confidence that the official received the treatment, we also included a gendered partner synonym. In addition, we chose surnames that have consistent interpretation as white across regions, to prevent variation in attitudes about race and ethnicity from influencing our findings (Crabtree and Chykina ). These were Anderson, Nielson, and Walsh.…”
Section: Methodsmentioning
confidence: 99%